The concept of calendar time of preschool children an exploratory study (2006)
The study explored preschool children's knowledge of calendar time. It investigated children's ability to identify and recognize the calendar days, as well as their knowledge of order of calendar days. Participants in the study were 38 preschoolers, ages four and five enrolled at the Child Development Laboratory of the University of the Philippines Los Baños. Data were gathered through a one-on-one interview with the children. Descriptive statistics were utilized to analyze children's responses. Findings showed that child-related activities and the regularity of going to school helped children in their concept of calendar time. Age, as a maturational factor facilitated the concept of calendar time of the preschoolers. Children's knowledge in the sequence of the calendar days comes later than their ability to identify and recognize the parts of the week. Seemingly, parental work schedule influenced children's concept of calendar time.
Keywords: Preschool education